Principios bioéticos en la prevención de la mala practica profesional en odontología - Jaya Guebla, Katherine Maribel (2023)
ABSTRACT: This research work includes the analysis of the importance of the bioethical principles applied during the clinical practice of dentistry and how subtracting its value would produce a dangerous and meaningless professional practice; it also describes a set of laws, norms and values that are attributed to those who provide their services around health. The present bibliographic review was elaborated based on the analysis of scientific articles in the dental field, databases such as: PubMed, ScienceDirect were used, the information was collected in a systemic and organized way, focused on the bioethical principles for the prevention of dental malpractice, information comprised between 2012 to 2022; the selection of articles allowed obtaining 52 articles. After the analysis of the information collected, it is concluded that malpractice claims are caused by professionals with little or a lot of work experience, it is because we are human beings capable of making mistakes. However, the significant difference lies in whether the mistake was intentional or unintentional. Even so, any act committed against the benefit of the patient is held responsible by the professional, to whom the laws of the state will be applied. Finally, it is concluded that to prevent all types of malpractice during the practice of the profession, it is necessary to promote ethical education programs, to generate professionals with ethical reasoning and professional responsibility during all patient care.